LEXICAL SEMANTIC ANALYSIS OF BUSINESS TERMINOLOGY IN APPLIED LINGUISTICS - Kamilova Durdona (Scholars Digest Publishing, 2023)
The scientific article substantiates the need to study the use of business terminology and analyze language and communication activities in the context of the business field, as a promising interdisciplinary field of applied linguistics. The socio-historical conditions of the emergence of new directions are described, the subject, methodology and practical importance, directions of its interaction with similar networks are defined. A discursive approach is proposed as a basis for research, in connection with which the concept of business discourse is introduced.
Keywords: terminology, linguistics, applied linguistics, business, business discourse, business field.